Late‐onset achalasia after esophageal atresia repair. Issue 3 (9th December 2011) - Marinello, F. G.; Targarona, E. M.; Poca, M.; Mones, J.; Hernández‐Ballesteros, C.
SUMMARY The development of achalasia in a patient with a history of esophageal atresia (EA) is rare. Here, we report a patient who had undergone surgery for EA at birth and presented achalasia at 30 years of age. He was successfully treated with laparoscopic surgery.